Penambahan Prebiotik Oligofruktosa dan Enzim Fitase Dari Aspergillus Niger pada Pakan yang Mengandung Wheat Pollard Terhadap Performa Broiler - Suci Wulandari; Dadik Pantaya; Ujang Suryadi (Jurnal Ilmu Peternakan Terapan, 2018)
This study was conducted to determine the effect of the addition of prebiotic oligofructose and phytase enzymes in feed containing wheat pollard on the performance of broiler. Oligofructose was added in feed 2 g/kg and phytase enzyme dose 500 U/kg. Parameters measured were broiler performance. One hundred broiler on 14 through 28 days were divided into 5 treatments: feed added P from dicalcium phosphate (P1), control feed (P2), feed added oligofructose (P3), feed added 2 g/kg phytase enzyme from Aspergillus niger (P4), and feed added a combination of oligofructose 2 g/kg and phytase enzyme dose of 500 U/g (P5). The data was analyzed to use Completely Randomized Design (CRD), if there was differences in further tests to be followed by Duncan's Multiple Range Test (DMRT). The results showed the feed containing high P, oligofructose addition, phytase enzyme, combination between oligofructose and phytase enzyme showed improvement of broiler performance on 14 to 28 days.